Soil metal(loid)s pollution around a lead/zinc smelter and source apportionment using isotope fingerprints and receptor models. (December 2021) - Liang, Xingyu; Wang, Chuan; Song, Zhengcheng; Yang, Shaochen; Bi, Xiangyang; Li, Zhonggen; Li, Ping
Abstract: Soil pollution from metal(loid)s has become a severe environmental issue. Source identification of soil metal(loid)s is the basis for pollution prevention and control. In this study, a total of 31 surface soil samples were collected from farmland near a large lead/zinc (Pb/Zn) smelter in Zhuzhou City, central China. The sources of soil metal(loid)s pollution were identified with principal component analysis/absolute principal component scores (PCA/APCS), positive matrix factorization model (PMF), and Pb isotope fingerprints. Results showed significant accumulation of metal(loid)s in agricultural soils. The averages of soil Cd, Pb, and Zn concentrations were 7.90, 273, and 675 mg kg −1, respectively. Metal(loid)s pollution was mainly distributed in the vicinity of the Pb/Zn smelter and the soil metal(loid)s contamination near the surface was quite high. The sources of metal(loid)s included Pb/Zn smelting, waste incineration, and natural sources. Smelting was the major source of metal(loid)s pollution. The Pb binary isotope mixing model indicated that smelting contributed 74.4% of soil Pb. PCA/APCS showed that smelting contributed 70.3%, 80.6%, and 86.5% to soil Cd, Pb, and Zn, respectively, while PMF revealed that it accounted for 73.1%, 72.1%, and 70.6%, respectively. Our study demonstrated that the combination of receptor models and isotope methods was comprehensive and effective for source identification, which provided new insights into determining the sources of soil metal(loid)s pollution. Graphical abstract: Image 1 Highlights: Obvious enrichment of soil Cd, Pb, and Zn was found in study area. Pb isotope fingerprints, PCA/APCS, and PMF were used to trace soil metal(loid)s. The sources of soil metal(loid)s included Pb/Zn smelting, waste incineration, and natural sources. Pb/Zn smelting contributed over 70% of soil metal(loid)s contamination.